Improving K-12 Classroom Literacy Instruction with the Model of the Complete, Literate Student: Shared Perspectives by MSEd Reading Program Graduates - Johannah Baugher (The Advocate, 2023)
The purpose of this study was to examine the impact of an instructional model, used in a Master of Science in Education in Reading (MSEd) Reading program, on K-12 classroom literacy instruction. Recent, MSEd Reading program graduates had an opportunity to share their perspectives on The Model of the Complete, Literate Student. Findings from this research study will be utilized to better understand the impact of this instructional model on K-12 classroom literacy instruction, as well as current practitioners’ professional growth as literacy leaders.
Keywords: literacy; intervention; instructional model